The Possibility of Using the Geographical Information Systems in the Pipe Transport of the Armed Forces of Slovakia - Juraj Sluka; Zdenek Dvorak; Lenka Rostekova (Communications - Scientific letters of the University of Zilina, 2005)
The paper describes possibilities of the geographical information systems’ usage in the pipe transport. All parts of information systems including hardware, software, peopleware, dataware and orgware are in a continuous process of development. Advantages and disadvantages of GISs are their important part. Pipe transport is part of transport provision in Slovakia. The Armed Forces of the Slovak Republic are preparing universal units for usage throughout the whole world. The pipe transport supported by a GIS is able to move different liquids into all crises places.